The modulating effect of coat color mutations on the generation and neutralization of reactive oxygen species in the Аmerican mink (Neovison vison) as a model - S. N. Sergina; V. A. Ilyukha; I. V. Baishnikova; T. N. Ilyina (Вавиловский журнал генетики и селекции)
The influence of gene mutations encoding coat color on parameters of reactive oxygen species (RO S) generation and neutralization in six organs of the mink (Neovison vison) was evaluated. The study was conducted with standard dark brown (+/+), monorecessive royal pastel (b/b) and silver-blue (р/р), and direcessive sapphire (a/a р/р) mutant minks. It was found that the functioning of both RO S generation and neutralization systems was genotypespecific. The direcessive sapphire (a/a р/р) combination induced high levels of antioxidant enzymes’ activities as well as of thiobarbituric acid-reactive products (TBА-RPs), characterizing lipid peroxidation level. In heart tissue, coat color mutations exerted modulating effects on both RO S generation and the level of low-molecular-weight antioxidants. The royal pastel (b/b) genotype showed the highest level of RO S generation, and the sapphire (a/a р/р), the lowest (statistically significant difference from standard). Coat color mutations modulate the dintensity of RO S generation and neutralization in lung tissue. On the one hand, royal pastel (b/b) in comparison with standard dark brown (+/+) decreases the total level of RO S generation, and on the other hand, it increases the level of generation of superoxide anion-radicals. Cluster analysis, presented in a combined dendrogram, showed that royal pastel (b/b) and sapphire (a/a р/р) minks, the farthest from standard (+/+), had the greatest modulating effects. It is reasonable to suggest that such effects contributed to the genetic plasticity of American mink in the course of colonization of North America and then during mink introduction in Northern Eurasia and South America.